Environmental tax reform roles and strategies of local governments: A quasi-natural experiment from China - Tianyang Chu (Sustainable Futures)
Whether environmental tax reform can drive green economic transformation is closely related to local government behavior. This study examines the impact of environmental tax reform on local governments using panel data for 247 Chinese prefecture-level cities from 2011 to 2021 and the difference-in-differences method. It finds that environmental tax reform leads local governments to increase environmental supervision and fiscal technology expenditure. A mechanism analysis shows that environmental tax reform increases local governments’ motivation to promote green innovation through target adjustments and public environmental demands. Heterogeneity analyses indicate that environmental tax reform has a stronger effect on increasing environmental supervision and fiscal technology expenditure in high-growth- and high-environmental-pressure cities, and northern cities. Expansion analyses show that although environmental tax reform inhibits overall market segmentation, it is more significant in southern cities and insignificant in northern cities. Finally, with active local government cooperation, environmental tax reform could reduce pollution emissions and promote green economic transformation.